2014
DOI: 10.1074/jbc.m114.609396
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Stefin B (Cystatin B) in Inflammation and Endotoxemia

Abstract: Background:The lack of cysteine cathepsin inhibitor, stefin B (cystatin B), results in progressive myoclonus epilepsy, type 1. Results: Stefin B deficiency in macrophages resulted in increased inflammasome activation. Conclusion: Stefin B-deficient mice are significantly more sensitive to e LPS-induced sepsis due to increased caspase-11 expression and mitochondrial damage. Significance: Stefin B has an important role in limiting the inflammatory response during LPS-induced sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 67 publications
7
57
2
Order By: Relevance
“…In fact, lower serum levels of cystatin C, considered the “dominant” cystatin (77), are associated with numerous inflammatory conditions (66), including sterile inflammatory arterial disease (78). Furthermore, cystatin B deficiency in mice exacerbated LPS-induced sepsis and elevated IL-1β levels in the serum (79). This latter study demonstrated higher caspase-1 and/or -11 activity and mitochondrial ROS, suggesting that loss of cystatin B increased inflammasome activation (79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, lower serum levels of cystatin C, considered the “dominant” cystatin (77), are associated with numerous inflammatory conditions (66), including sterile inflammatory arterial disease (78). Furthermore, cystatin B deficiency in mice exacerbated LPS-induced sepsis and elevated IL-1β levels in the serum (79). This latter study demonstrated higher caspase-1 and/or -11 activity and mitochondrial ROS, suggesting that loss of cystatin B increased inflammasome activation (79).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cystatin B deficiency in mice exacerbated LPS-induced sepsis and elevated IL-1β levels in the serum (79). This latter study demonstrated higher caspase-1 and/or -11 activity and mitochondrial ROS, suggesting that loss of cystatin B increased inflammasome activation (79). However, the authors noted that there were no signs of LMD or elevated cathepsin activity in the cytosol, and effects on pro-IL-1β were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic activities and proteins resembling, related, or being even identical with endo-lysosomal proteases have been detected in the cytoplasm, the mitochondria, and the nucleus (Dall and Brandstetter 2013;Duncan et al 2008;Goulet et al 2004;Haugen et al 2013;Maher et al 2014;Sullivan et al 2009;Tamhane et al 2014;Tedelind et al 2010). Below, we will outline possible pathways and cell biologically meaningful processes in an attempt to explain the occurrence of endolysosomal proteases and/or variants thereof in such highly unexpected locations.…”
Section: Endo-lysosomal Cysteine Peptidases: Myths and Common Questionsmentioning
confidence: 99%
“…CSTB is highly expressed in immune cells, e.g., in blood leukocytes, hepatic lymphocytes, placental macrophages, and microglia [5–9], and it is upregulated in vitro by pro-inflammatory stimulation [8, 10, 11]. In immune cells, the function of CSTB has been linked to chemotaxis [8], expression and secretion of cytokines, and release of nitric oxide [10, 12, 13], implying a role in the immune response. CSTB function has also been associated with diverse cellular processes, such as regulation of apoptosis [14, 15], bone resorption [16, 17], protection of neurons from oxidative stress [18], and cell cycle progression [19].…”
Section: Introductionmentioning
confidence: 99%